2018
DOI: 10.1002/jso.25062
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node metastasis in primary cutaneous basosquamous carcinoma. A cross‐sectional study

Abstract: Cutaneous BSC is associated with early nodal metastatic potential. Tumor size >2 cm, lymphatic and perineural invasion are significant determinants for SLN micrometastasis. In the absence of palpable lymphadenopathy, wide resection and SLNB with long-term follow-up are highly recommended in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, there is open controversy regarding whether SLNB should be offered in BSCs for the early diagnosis of occult nodal metastasis, staging and treatment of subclinical node disease [ 17 , 27 ]. Kakagia et al, in a prospective study with 142 patients with BSC, concluded that tumor size >2 cm in addition to lymphatic and perineural invasion are significant determinants of SLN micrometastasis [ 46 ]. In the absence of palpable lymphadenopathy, wide resection and SLNB with long-term follow up is highly recommended in these patients [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is open controversy regarding whether SLNB should be offered in BSCs for the early diagnosis of occult nodal metastasis, staging and treatment of subclinical node disease [ 17 , 27 ]. Kakagia et al, in a prospective study with 142 patients with BSC, concluded that tumor size >2 cm in addition to lymphatic and perineural invasion are significant determinants of SLN micrometastasis [ 46 ]. In the absence of palpable lymphadenopathy, wide resection and SLNB with long-term follow up is highly recommended in these patients [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kakagia et al, in a prospective study with 142 patients with BSC, concluded that tumor size >2 cm in addition to lymphatic and perineural invasion are significant determinants of SLN micrometastasis [ 46 ]. In the absence of palpable lymphadenopathy, wide resection and SLNB with long-term follow up is highly recommended in these patients [ 46 ]. However, a possible “preventive benefit” of early SLNB for the nodal spread and distant metastasis needs further prospective controlled studies, with a longer follow-up period, in order to be confirmed [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, cases of successful sentinel lymph node sampling to detect nodal metastasis in BCC, particularly basosquamous cell carcinoma, have been published [10]. Further research is required to determine which patients would benefit from this approach, in particular those with lesions measuring >20 mm and/or perineural/lymphatic invasion [11].…”
Section: Discussionmentioning
confidence: 99%
“…Perineural growth, also referred to as perineural invasion, is a classic indicator of aggressive disease for any cutaneous malignancy (Buchanan et al, 2014). Along with a tumor size >2 cm and lymphatic invasion, perineural involvement is a significant determinant for sentinel lymph node micrometastasis (Kakagia et al, 2018).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
“…Another study evaluated 1,000 consecutive Mohs cases and found that two of 228 cases of patients with SCC had pulmonary metastases (0.87%), compared with two of 27 patients with BSC (7.4%) (Bowman et al, 2003). Similarly, a more recent study revealed that 11 of 142 (7.7%) patients with BSC had sentinel lymph node micrometastasis (Kakagia et al, 2018). Furthermore, whether BSC arises de novo or originates from a pre-existing BCC continues to be under debate.…”
Section: What Is False About the Management And/or Prognosis Of Basosmentioning
confidence: 98%